2006
DOI: 10.1051/apido:2006048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of scent deposits on flower choice: experiments in an artificial flower array with bumblebees

Abstract: -Foraging bumblebees leave chemical substances when visiting flowers and the detection of these "scent marks" improves their foraging efficiency. Whereas laboratory studies found that scent-marks convey attraction to food sources, all field studies found foragers to be repelled by recently visited flowers. In this study we aim to resolve this conflict by implementing near-natural reward dynamics in a laboratory feeder array. When feeders were filled with small, non-replenished amounts of reward, worker bumbleb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…On the other hand, some studies report the contrary (e.g. Witjes and Eltz, 2007). Finally, other studies showed that bees react to scent marks as a function of their previous experience (Leadbeater and Chittka, 2009;.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, some studies report the contrary (e.g. Witjes and Eltz, 2007). Finally, other studies showed that bees react to scent marks as a function of their previous experience (Leadbeater and Chittka, 2009;.…”
mentioning
confidence: 98%
“…There was also no clear indication that the bees learned to choose the flower without contamination over the duration of the study period, indicating that the avoidance of the contaminated flower is an innate response. Finally, bees more often switched to the rewarding flower after landing on the nonrewarding, contaminated flower (Fig.2D), emphasising the repellent effect of contamination for the bees.Scent marks and their significance have been well studied (Goulson et al, 1998;Goulson et al, 2000;Goulson et al, 2001;Leadbeater and Chittka, 2009;Leadbeater and Chittka, 2011;Saleh et al, 2007;Witjes and Eltz, 2007;Witjes and Eltz, 2009). On the one hand, some studies have shown that scent marks act as repellents for experienced bees, allowing them to choose rewarding flowers more efficiently, as previous visitors might have reduced the available nectar (Goulson et al, 1998;Goulson et al, 2001).…”
mentioning
confidence: 99%
“…In laboratory experiments scent marks were found to be either repellent (Witjes and Eltz 2007) or attractive (Cameron 1981;Schmitt and Bertsch 1990), depending on whether the reward in feeders could be depleted during a single visit or not. These behavioural differences could certainly be because of flower marking with chemically different 'attractant' or 'repellent' pheromones.…”
Section: Discussionmentioning
confidence: 99%
“…These behavioural differences could certainly be because of flower marking with chemically different 'attractant' or 'repellent' pheromones. However, a much more parsimonious explanation is that the same chemical cue (footprint) can adopt opposite meanings for foragers because of negative or positive conditioning (Saleh and Chittka 2006;Witjes and Eltz 2007). Chemical cues inherent to footprints are used in variable contexts by other Hymenoptera.…”
Section: Discussionmentioning
confidence: 99%
“…The repellent effects decrease with the replenishment of nectar volume, and the duration of the effect differs among flower species (Stout and Goulson, 2001). Regarding the different roles of scent marks, several studies have shown that different responses to the scent marks could result from different interpretation of the same chemicals according to the abundance of resources and the context in which they are presented (Saleh and Chittka, 2006;Witjes and Eltz, 2007).…”
Section: Introductionmentioning
confidence: 99%